Participation of Political Parties in Local Governments of Nepal (Patan Pragya, 2022)
The success and failure of the political economy depend on the structure and function of political parties. The agenda of development in a democratic country is set and met by ruling political parties. Political parties are dynamic forces to mobilize mass for achieving common agendas. Political parties play an effective and efficient role in political socialization of citizens. In Nepal, political parties are mostly capable of creating public awareness about the common concern. Political parties produce both positive and negative impacts on all dimensions of society in Nepal. To analyze the status of political parties in the local governance of Nepal, and to explore their role, strengths and weaknesses in the local development of Nepal, this article is prepared with the title ‘Participation of political parties on local level government in Nepal”. It is mainly based on the secondary data of the election commission of Nepal. Information regarding objectives was collected through various search engines by a simple literature review. The status of political parties is found unequal at the local level of government in Nepal. Nepali congress party occupies the first position followed by CPN-UML and CPN-Maoist respectively in second and third positions. Local-level Governments must play effective roles to solve the day-to-day immediate problem of people. The joint efforts of all political parties are mandatory to meet the immediate requirement of local people through the effective mechanism of service delivery. The role and responsibility of political parties are vital to fulfilling gaps between service consumers and providers. Lack of coordination, unhealthy competition, and lack of transparency in political parties are notable issues to address without delay. To meet the common concern of Nepalese people regarding their local issues, joint efforts of all political parties are mandatory.